EGGS, LARVAE AND JUVENILES OF THE INDIAN SPRAT, SARDINELLA JUSSIEU (LACEPEDE) - Bensam, P (Indian Journal of Fisheries, 2011)
Sardinella jussieu = Sardinella gibbosa (Bleeker), popularly known as the Indian sprat, is one of the commercially important sardines occurring in Indian coastal waters. No adequate information is available hitherto on the early development of this fish although work- was in progress on some aspects of its fishery and biology (Devanesan, 1932; Chacko, 194(5, 1950; Sekharan, 1955, 1959; Ganapati and Rao, %1957; Dharmamba, 1959; Bennet, 1961; Dutt, 1961). While examining the plankton collected off Cannanore, south-west coast of India (surface hauls from the 6-fathom station sampled by a | metre net of fine organdie cloth), during January-May 1964, a search for the eggs and larvae of S. jussieu was made because partly and fully spawned specimens appeared in large numbers in the local catches of both indigenous crafts and mechanised vessels.